VD_FINDINFO HC / 2017 / 819 vom 29. Juni 2017 - VD Tribunal cantonal (2017)
COMPÉTENCE INTERNATIONALE, DOMICILE | 29 al. 2 Cst., 117 LDIP, 143 LDIP, 20 LDIP, 5 par. 1 let. a CL (2007), 59 par. 1 CL (2007), 151 CPC (CH)